Rationale for a Vitamin K2 and Vitamin D3 Intervention Trial in Children and Adolescents with Low-Energy Bone Fractures - Popko, MD, PhD, Janusz; Karpinski, MD, Michał; Guszczyn, MD, Tomasz; Chojnowska, Ph.D., Sylwia; Maresz, PhD, Katarzyna; Mehta, Ph.D., Dilip S.; Badmaev, MD, PhD, Vladimir; Stohs, PhD, Sidney J. (International Journal of Innovative Research in Medical Science, 2021)
Background: The role of vitamin K2, especially menaquinone-7, has recently been highlighted in the literature and distinguished from vitamin K1 in maintaining calcium homeostasis and a healthy skeletal system. Epidemiological and clinical research provides a new nutritional paradigm for efficient and safe delivery of calcium that requires co-supplementation with the fat-soluble vitamins D and K. Objective: We propose a prospective, three-month, randomized, double-blind, placebo-controlled intervention trial (RDBPC), investigating the effects of vitamin D3 in the presence and absence of vitamin K2 (menaquinone-7, MK-7) on the healing process of low-energy bone fractures in children and adolescents. Thus, information will be obtained regarding the role of vitamin K2 in the bone healing process. Methods: Ninety pediatric patients with low blood levels of vitamin D and low energy bone fractures will be divided into three groups that receive daily for three-month identical soft gel capsules containing 2000 IU vitamin D3, 90 mcg of vitamin K2 as menaquinone-7 (MK-7) combined with 2,000 IU D3 or olive oil-containing placebo. Patients will visit the clinic on weeks 1, 2, 4, 6, 8 and 12, and will be evaluated by X-ray regarding progress in bone union and range of joint motion. Blood samples will be collected in duplicates on day 0 and after the 3-month regimen. The blood samples will be analyzed for vitamin K (menaquinone-7, MK-7) and vitamin D as well as the bone turnover markers bone-specific alkaline phosphatase (BALP) and N-terminal telopeptide (NTX). Conclusions: This proposed nutritional regimen will provide new information regarding the ability of vitamins D3 and K (specifically MK-7) in combination therapy to heal and prevent low-energy fractures among children and young adults. It will also contribute to building the "bone bank," therefore helping to prevent the risk of fractures in adulthood and the development of osteoporosis later in life. ClinicalTrials.gov Identifier: NCT03871322